1998
DOI: 10.1074/jbc.273.19.11776
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrophobic Face Orientation of Apolipoprotein A-I Amphipathic Helix Domain 143–164 Regulates Lecithin:Cholesterol Acyltransferase Activation

Abstract: Apolipoprotein A-I (apoA-I) activates the plasma enzyme lecithin:cholesterol acyltransferase (LCAT), catalyzing the rapid conversion of lipoprotein cholesterol to cholesterol ester. Structural mutants of apoA-I have been used to study the details of apoA-I-LCAT-catalyzed cholesterol ester formation. Several studies have shown that the ␣-helical segments corresponding to amino acids 143-164 and 165-186 (repeats 6 and 7) are essential for LCAT activation. In the present studies, we examined how the orientation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 45 publications
(45 reference statements)
7
65
1
Order By: Relevance
“…Biochemical Characterization-ApoA-I acts as a cofactor for LCAT, and repeat 6 (residues 143-164) is thought to regulate this process (36,37), although residues 99 -120 (containing Met 112 ) may also participate (38). As can be seen in Table IV, the ability of drHDL A-I and drHDL A-Iϩ32 to activate LCAT was comparable.…”
Section: Resultsmentioning
confidence: 99%
“…Biochemical Characterization-ApoA-I acts as a cofactor for LCAT, and repeat 6 (residues 143-164) is thought to regulate this process (36,37), although residues 99 -120 (containing Met 112 ) may also participate (38). As can be seen in Table IV, the ability of drHDL A-I and drHDL A-Iϩ32 to activate LCAT was comparable.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that both His-⌬1-43 and His-⌬1-65 apoA-I were associated with decreases in LCAT activation relative to His-Wt apoA-I (Table II). The observation that these deletions affected LCAT activation is intriguing, because this property is generally associated with class A helices of the central domain, in particular helix 6 (29,46,47). Recent work suggests that a cluster of 3 arginine Arg residues at the interface of the hydrophilic and hydrophobic faces in helix 6 contributes to a specific locale of positive surface potential that may stimulate LCAT activity (48).…”
Section: The N Terminus Of Apoa-i Is Essential For Hdl Maturationmentioning
confidence: 99%
“…LCAT activation [6]. The C-terminal part of apo A-I was shown to be responsible for association with lipids [7], whereas the Nterminal part seems to be responsible for stabilizing its lipid-free structure [8,9].…”
Section: Ormentioning
confidence: 99%